Obcy w nas i my w obcym: przekład jako różnica i podobieństwo czy przypominanie - Tokarz, Bożena (Przekłady Literatur Słowiańskich, 2014)
A Stranger in Us and We in a Stranger: a difference and a similarity or a reminder The knowledge on translation, which was developed by different methodologies and different disciplines, fulfills the need of taking into consideration the structurally-artistic issues by comparative literary studies, most basic for literature and literary studies, occupying the central place in comparative literature. This shift in comparative interests is accompanied by a revealing lack of works undertaking research into developmental-typological regularities in general literature. Moreover, with the central position of translation in this discipline, it is paradoxical that resigning from text and its subject matter in favour of reception and the results of functioning of translation in the target culture has been declared. While the dislike for systemizing and typologizing facts of general literature is doubly hard because of the disapproval of dogmatic theories and the difficulties within research into the abundance of literary material, the target, the place, the circumstances and the way of functioning in time and in culture are inherent parts of the linguistically-artistic structure, that is, everything that is within interests of the contemporary culturally oriented literary studies. Key words: translation, comparative study, translation studies, hermeneutic, a „cultural turnabout”.